Measuring the biological effect of presurgical metformin treatment in endometrial cancer - Sivalingam, V N (Br J Cancer, 2016)
BACKGROUND: Preclinical studies in endometrial cancer (EC) show that metformin reduces cellular proliferation by PI3K-AKT-mTOR inhibition. We tested the hypothesis that short-term presurgical metformin reduces cellular proliferation in atypical endometrial hyperplasia (AEH) and endometrioid EC, and assessed the feasibility of using phosphorylated PI3K-AKT-mTOR proteins as tissue end points. METHODS: Women with AEH or EC received metformin 850 mg twice a day or no drug in the presurgical window between diagnosis and hysterectomy. Before and after the window, tissue samples were obtained; serum markers of insulin resistance (e.g. homeostasis model of assessment of insulin resistance index) were determined; and anthropometrics measured (e.g. BMI). Cell proliferation (Ki-67) and PI3K-AKT-mTOR phosphostatus were assessed by immunohistochemistry and scored blinded to treatment. RESULTS: Twenty-eight metformin-treated and 12 untreated patients, well matched for age and BMI, completed the study. Metformin treatment (median 20 days, range 7–34) was associated with a 17.2% reduction in tumour Ki-67 (95% CI −27.4, −7.0, P=0.002), in a dose-dependent manner. Tumour PI3K-AKT-mTOR protein phosphostatus varied but the effects were not significant after adjusting for changes in controls. CONCLUSIONS: Short-term metformin was associated with reduced Ki-67 expression in EC. Changes in tumour PI3K-AKT-mTOR protein phosphostatus were seen in both groups. Future studies should address the variability attributed to different sampling techniques including devascularisation of the uterus at hysterectomy.